2017
DOI: 10.2147/ijn.s122747
|View full text |Cite
|
Sign up to set email alerts
|

A novel ion-exchange carrier based upon liposome-encapsulated montmorillonite for ophthalmic delivery of betaxolol hydrochloride

Abstract: As a novel ion-exchange carrier with high surface area and excellent exchangeability, montmorillonite (Mt) was intercalated with betaxolol hydrochloride (BH) to form a nanocomposite and then encapsulated by liposomes (Mt-BH-LPs) for an ophthalmic drug-delivery system. The Mt-BH and Mt-BH-LPs were prepared by an acidification process and ethanol injection combined with ammonium sulfate gradient methods. The successful formation of Mt-BH and Mt-BH-LPs was verified by thermogravimetric analysis, X-ray diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 51 publications
(53 reference statements)
0
15
0
1
Order By: Relevance
“…The liposomal formulation consisted of Betaxolol Hydrochloride (BH) along with Montmorillonite (Mt) to form (Mt-BH-LP) in order to overcome poor ocular bioavailability. From this study, it was concluded that the developed and optimized Mt-BH-LP was effective in decreasing Intraocular Pressure (IOP) and maintaining higher ocular bioavailability [ 17 ].…”
Section: Need For Nanomedicine For Ocular Drug Deliverymentioning
confidence: 99%
“…The liposomal formulation consisted of Betaxolol Hydrochloride (BH) along with Montmorillonite (Mt) to form (Mt-BH-LP) in order to overcome poor ocular bioavailability. From this study, it was concluded that the developed and optimized Mt-BH-LP was effective in decreasing Intraocular Pressure (IOP) and maintaining higher ocular bioavailability [ 17 ].…”
Section: Need For Nanomedicine For Ocular Drug Deliverymentioning
confidence: 99%
“…Многим исследователям представляется перспективным для доставки гипотензивных препаратов использовать комбинации полимеров и коллоидных систем: липосом [22][23][24][25][26], ниосом [27,28], кубосом [29], микроэмульсий [30], наноэмульсий [31][32][33] и наночастиц [34][35][36][37][38][39][40]. За счет медленного высвобождения лекарственных препаратов удается значительно пролонгировать время нахождения активного вещества в глазу.…”
Section: обзоры литературыunclassified
“…[22][23][24] In our previous study, BH molecules (as cationic compounds) could be successfully intercalated into the interlayer space to form a complex carrier (Mt-BH), which showed significant controlled release. 25,26 Based on this, we tried to develop a novel ion-exchange controlled-release delivery system to improve bioavailability and compliance of topical ophthalmic preparation for glaucoma treatment. In the present study, with the intercalation of BH into the interlayer space of the clay, the structure was further integrated with chitosan NPs.…”
Section: Introductionmentioning
confidence: 99%